SOCIAL RETURN ON INVESTMENT (SROI) ANALYSIS ON CREATING SHARED VALUE (CSV) PROGRAM WITH THE THEME “SAYURPRENEURSHIP 4.0 TALK SHOW: DIGITALIZATION STRATEGY FOR VEGETABLE TRADERS” - Aldo Lovely Arief Suyoso; Gancar Candra Premananto; Norizah Binti Mohd Mustamil (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
SROI helps measure and communicate the value of social investment by taking into account the benefits received by the community and other stakeholders. SROI can assess the extent to which the digitalization program has succeeded in providing positive impacts, both in terms of increasing the income of vegetable traders and from other social aspects, such as improving the quality of life and welfare. Companies or organizations can contribute to the welfare of the community while improving their business performance through the CSV program. CSV can help create solutions that benefit vegetable traders, as well as the surrounding community by utilizing digital technology to improve the way they operate and interact with the market. Programs like this, if carried out in the long term, are expected to encourage digital transformation in the traditional trade sector, creating a more modern and competitive business ecosystem. The results of this literature study indicate that increasing awareness, skills, and income for vegetable traders, support for local MSMEs, and promotion of more environmentally friendly business practices. These positive impacts are not only felt in the short term but also have the potential to provide sustainable long-term benefits, supporting local economic growth and environmental sustainability. With this high SROI ratio, this event can be considered very effective and efficient in achieving its goals, as well as providing returns that far exceed the investment made.